Mapping linguistic landscapes: Exploring affective regimes of Chinese New Year culture in Bangkok - Bin Lang; Kanokporn Numtong (Cogent Arts & Humanities)
Urban spaces serve as affective landscapes, embodying a novel research perspective and direction within the study of linguistic landscapes. This research delves into the linguistic composition of commercial signage within Bangkok’s urban fabric, focusing on the linguistic and semiotic landscape of public commercial spaces. It investigates the organization and narration of the societal affects surrounding Chinese New Year culture, thereby shaping the city’s ethos. The famous Chinese community (Yaowarat Road Chinatown) and renowned commercial hub (Siam commercial district) in Bangkok contributed a total of 236 images depicting Chinese New Year cultural symbols for this study. By employing theories of nexus analysis and place semiotics comprehensively, this research elucidates how linguistic practices within the Chinese New Year festive landscape engender and influence urban affects. The findings underscore that commercial districts, as pivotal agents, craft the urban portrayal of Chinese New Year culture through linguistic and semiotic landscapes, offering residents and tourists alike an affective voyage through exotic customs and New Year traditions. The carriers, emplacement and inscriptions of spatial discourses reflect the attitudes and philosophies of landscape planners who advocate for New Year cultural customs. Furthermore, the interaction order within the landscapes reflects both explicit New Year interactive activities and implicit New Year semiotic artifacts, collectively contributing to the construction of the urban narrative steeped in New Year’s cultural essence. This research into Bangkok’s urban landscapes of New Year affective regimes enriches the understanding of the symbiotic relationship between language and urban affective economies in practical terms.